Integrasi Prinsip Syariah dalam Pengembangan Fintech: Tantangan dan Peluang - Sulistiawati, Ade; Safri, Aisyah; Arimbi, Andi Asira; Hastuty, Ade (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
This study aims to conceptually examine the process of integrating sharia principles in the development of sharia financial technology (fintech), as well as identify the challenges and opportunities that accompany it in Indonesia. Using a qualitative approach through a literature study, this research examines academic literature, policy documents, and related fatwas obtained from various credible sources such as scientific journals, official websites of OJK, DSN-MUI, and KNEKS. The analysis was conducted thematically and content-wise on key issues such as the application of sharia contracts (murabahah, mudharabah, musyarakah), the supervision of the Sharia Supervisory Board, and the application of technology such as smart contracts and blockchain in maintaining sharia compliance. The results show that the integration of sharia principles in fintech systems and products faces a number of challenges, including low sharia financial literacy, limited regulations, lack of human resources who are experts in digital muamalah fiqh, and not optimal sharia technology support. However, the growth potential of this industry is huge, supported by the majority Muslim population, the need for halal financial services, as well as regulatory initiatives and the development of digital technology. This research is expected to provide theoretical and practical contributions for regulators, industry players, and Muslim communities in supporting the growth of Islamic fintech that is inclusive, sustainable, and in accordance with maqashid al-shariah